Observations on Reproduction and Behavior of Captive Philippine Crocodiles (Crocodylus mindorensis Schmidt) - Alcala, Angel C.; Alcala, E. L.; Ross, C. A. (Silliman Journal, 2024)
A breeding facility for the endangered Philippine Crocodile (Crocodylus mindorensis Schmidt) was established in 1980 at Silliman University, Dumaguete City, Philippines. As of February 1984, the breeding program has produced 21 surviving juveniles raging from hatchling to 3 years of age. Observations on the behavior of the captive adults and juvenile crocodiles are described. Courtship, mating and nest building occured each year between January and May. Eggs were laid variously between April and August during the years 1981-1984 ; with multiple clutches by the same female in 1981-1982. The mean clutch was 15.7 (range: 7-25). The incubation period was 77 to 85 days. The female remained near the nest during incubation, and for that period and a few months thereafter was very aggressive. Vocalization of piped young cued the female to open the nest and transport the hatchlings or eggs to the water. Hatchlings and young were very wary of human intruders. Fighting among the young resulted from close confinement.